The Legal Status of Jerusalem in Israel-Palestine Conflict After Donald Trump’s Statement: In Terms of International Law - Ernest Nasarius Firmandani (Fakultas Hukum Universitas Hang Tuah, 2018)
Jerusalem is a holy city for three celestial religions involved in Arab-Israeli conflict, which has lasted for approximately 70 years. Due to its strategic geographical conditions, Jerusalem is taken into account in politic, economy, and security affairs. Since 1967, the status of Jerusalem has been de facto occupied and controlled by Israel, not clearly de jure. The UN established the UN General Assembly Resolution 181 on the division of Palestinian territory. However, Israel did not comply with that. Such tension became further heated after the US President, Donald Trump, in his statement on December 2017, formally recognized Jerusalem as the capital city of Israel. This decision evoked discontent from leaders across the world as it threatened the stability across region and destroyed the prospect of achieving peacefulness between Israel and Palestine. Although this statement is a form of recognition of sovereignty, it is considered against the principle of estoppel.